STUDI LITERATUR: EFEKTIFITAS PENYULUHAN TRIAD KRR (SEKSUALITAS, HIV/AIDS DAN NAPZA) TERHADAP PENGETAHUAN REMAJA - Sugianto Sugianto (Elsia: Jurnal Psikologi Manusia, 2022)
Adolescence or also known as adolescence is a period of transition from childhood to adulthood which includes all its natural developments as a preparation for entering adulthood. Being a teenager means going through a tough process, which requires teenagers to have very complex problems along with the transition period they are experiencing, the most prominent problem in adolescents is social problems. The aim is to find out how effective the TRIAD KRR counseling (Sexuality, HIV/AIDS, and Drugs) is on youth knowledge. The method in this study uses a descriptive narrative design with a literature review approach (literature study). A literature review study is a synthesis of the literature on a research topic. This literature search used the Google Scholar and IOS electronic database with the keywords counseling, TRIAD KRR (Sexuality, HIV/AIDS and Drugs) and youth knowledge. There are 5 literatures that meet the inclusion criteria, within the last 5 years. Based on the literature study used as comparative material, it was found that from the five literatures above regarding TRIAD KRR counseling is very important for adolescents who are the successors to the nation's future generations. This is intended as a preventive measure for teenagers so they don't fall into drug use, free sex, to abortion which is the final choice of teenagers. The conclusion is that the effectiveness of TRIAD KRR counseling (Sexuality, HIV/AIDS, and Drugs) on adolescent knowledge is very influential or very effective.